THE CATALOG OF CORRECTIONS TO THE DECLINATIONS OF 186 FK4 STARS - Myalkovskiy, M. I. (Одеські астрономічні публікації, 2017)
The catalog of corrections to the declinations of 186 fk4 stars is presented